2015
DOI: 10.1002/ajpa.22743
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: A linear model for predicting δ13Cprotein

Abstract: The model presented here appears to hold significant potential for the prediction of the carbon isotope signature of dietary protein using only such data as is routinely generated in the course of stable isotope analysis of human osseous remains. These predicted values are ideal for use in multisource mixture modeling of dietary protein source contribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 48 publications
(114 reference statements)
1
13
0
Order By: Relevance
“…The two highlighted combinations (3:1 C 3 :C 4 protein and energy versus 1:3 C 3 :C 4 protein and energy) in Table 6 represent the best approximations of the end-member dietary combinations seen in the Larache individuals (3,802 and 360, respectively), with the remaining individuals falling somewhere between these extremes. Similar results for modeled dietary protein (displayed in Table 3) are obtained using the formula proposed by Pestle et al (2015). These modeled solutions are testament to the fact that some individuals (with lower d 13 C collagen and d 13 C apatite values) were subsisting on C 3 -foddered terrestrial fauna and C 3 carbohydrates, similar to individuals from the Loa Basin , central Chile (Falabella et al, 2007), and central western Argentina (Gil et al, 2006), whereas others were likely consuming a large portion of C 4 -foddered terrestrial fauna and C 4 plants, much more like individuals from coastal and highland Peru (Finucane et al, 2006;Kellner and Schoeninger, 2008).…”
Section: Stable Carbon and Nitrogen Isotope Datasupporting
confidence: 74%
“…The two highlighted combinations (3:1 C 3 :C 4 protein and energy versus 1:3 C 3 :C 4 protein and energy) in Table 6 represent the best approximations of the end-member dietary combinations seen in the Larache individuals (3,802 and 360, respectively), with the remaining individuals falling somewhere between these extremes. Similar results for modeled dietary protein (displayed in Table 3) are obtained using the formula proposed by Pestle et al (2015). These modeled solutions are testament to the fact that some individuals (with lower d 13 C collagen and d 13 C apatite values) were subsisting on C 3 -foddered terrestrial fauna and C 3 carbohydrates, similar to individuals from the Loa Basin , central Chile (Falabella et al, 2007), and central western Argentina (Gil et al, 2006), whereas others were likely consuming a large portion of C 4 -foddered terrestrial fauna and C 4 plants, much more like individuals from coastal and highland Peru (Finucane et al, 2006;Kellner and Schoeninger, 2008).…”
Section: Stable Carbon and Nitrogen Isotope Datasupporting
confidence: 74%
“…The estimated fractional contribution of dietary protein to collagen varied by species, about 63% for the two rat studies, 80% for mice, and 83% for pigs. Pestle et al [20] derived a similar regression model to predict the δ 13 C values of dietary protein from isotopic measurements of apatite and collagen. They reported that their model residuals differed significantly between pigs (n = 15) and rodents (n = 21), implying differences in how these organisms processed protein and energy sources into collagen.…”
Section: Protein Content Controlled Metabolic Routingmentioning
confidence: 99%
“…The present work adds 19 individuals to a previously published sample of 12 individuals from Ancachi/Quillagua (Pestle, Torres‐Rouff, Gallardo Ibanez, Andrea Cabello, & Smith, ). Ultimately, we consider both the internal variability and structure of the paleodiet of these individuals and then position them against a larger regional sample of nearly 200 previously analyzed individuals from the Formative Period (Pestle, ; Pestle, Torres‐Rouff, Hubbe, Santana, Pimentel, Gallardo, & Knudson, ; Pestle, Torres‐Rouff, Gallardo, Ballester, & Clarot, ).…”
Section: Methodsmentioning
confidence: 99%